1987
DOI: 10.12935/jvma1951.40.167
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Canine Babesiosis in Aomori Prefecture

Abstract: We encountered 19 cases of canine babesiosis which were not previously reported in Aomori prefecture. The main clinical signs were depression, decrease of appetite, excretion of brownish urine and pallor of the visible mucous membrane. A remarkable regenerative anemia was peculiar in blood examinations. On Giemsa stained blood smears, parasitism of small protozoa was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This finding is similar to that found in a study reported 17 years ago [13]. In addition, a significant proportion of Tosa dogs (29.8%) were carriers of B. gibsoni in Aomori Prefecture, Japan.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is similar to that found in a study reported 17 years ago [13]. In addition, a significant proportion of Tosa dogs (29.8%) were carriers of B. gibsoni in Aomori Prefecture, Japan.…”
Section: Discussionsupporting
confidence: 91%
“…In Japan, it is distributed mainly in the western part [3,4,7,8] and only a few epidemiological and clinical studies have been reported on canine B. gibsoni infection in eastern Japan. All of the confirmed cases of B. gibsoni infection in the eastern part of Japan were found among Tosa dogs, a fighting breed raised only in Aomori Prefecture [3,10,17]. Transmission of B. gibsoni in this area was thought not to occur via ticks [3], although the vector tick species, Haemaphysalis longicornis, is distributed throughout Japan [19].…”
mentioning
confidence: 99%
“…They were maintained in the laboratory by feeding on rabbits for several generations. The strain of B. gibsoni used was originally was isolated from naturally infected dogs in the Towada area in Aomori Prefecture, and maintained in the laboratory by passage through dogs [3]. Five splenectomized mongrel dogs, 9 to 12 months old, were used for transmission of the parasite.…”
mentioning
confidence: 99%